Analisis Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Layanan Masyarakat Pada Kantor Desa Klampok Kecamatan Wanasari Kabupaten Brebes - Melani Ade Zumarnis; Nur Khojin; Andi Yulianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The services provided to the community must be in accordance with the rules set by government regulations, service officers cannot provide services as they please because the services provided involve many people, because even one person gets the wrong service, the community will perceive it positively. or negativeThe aim of this research is to analyze the influence of service quality and facilities on community service satisfaction, the influence of service quality on community service satisfaction and the influence of facilities and service quality together on community service satisfaction. This research used a quantitative type of research with a sample of 99 respondents who were residents of Deesa Klampok Kec. Wanasari, BrebesRegency.Thiscollection technique uses questionnaire techniques, interviews/observations and analysis techniques in this research use the classic assumption test, hypothesis test (t test and F test). This research data processing uses the SPSS version 25 software program. The results of this research show that there is an influence of service quality on community service satisfaction. The results of this research show that there is an influence of facilities on community service satisfaction. The results of this research show that together the influence of service quality and facilities influences community service satisfaction.